2010
DOI: 10.4314/ajnt.v3i1.57594
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidemia among Sudanese Children Undergoing Maintenance Dialysis

Abstract: Introduction: Dyslipidemia is an established risk factor for atherosclerosis and cardiovascular disease. It is common among children undergoing maintenance dialysis. To our knowledge, this is the first report on the lipid profile of children undergoing maintenance hemodialysis (HD) or continuous ambulatory peritoneal dialysis (CAPD) in Sudan. Methods:We studied 17 children on HD, 11 children on CAPD and 28 controls. The levels of total cholesterol (TC), triglycerides (TGD) and high density lipoprotein choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…In the present study, serum phosphate and potassium were significantly higher while serum calcium was significantly lower and parathyroid level was higher in case group than control. This finding in concordance with Ali et al 18 who reported the same results. But in present study hyperkalemia, hypocalcemia, hyperphosphatemia, all these derangements were not statistically significant between stages except hyperparathyroidism.…”
Section: Introductionsupporting
confidence: 93%
“…In the present study, serum phosphate and potassium were significantly higher while serum calcium was significantly lower and parathyroid level was higher in case group than control. This finding in concordance with Ali et al 18 who reported the same results. But in present study hyperkalemia, hypocalcemia, hyperphosphatemia, all these derangements were not statistically significant between stages except hyperparathyroidism.…”
Section: Introductionsupporting
confidence: 93%